2021
DOI: 10.5607/en20051
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Exhibits Neuroprotective Effects against Mitochondrial Complex I Inhibition via Regulating Apoptotic Signaling

Abstract: Nobiletin, a polymethoxylated flavonoid found in citrus, has been studied because of its modulatory functions in cellular signaling cascades, and effects to prevent mitochondrial calcium overload and neuronal cell death. Particularly, we previously reported that nobiletin induced changes in the mitochondrial membrane potential through K + channel regulation, suggesting that nobiletin might exert neuroprotective effects via regulating mitochondrial functions associated with the electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Several studies have demonstrated that NOB plays an important role in modulating mitochondrial function, including influencing the mitochondrial membrane potential [ 20 , 21 , 22 , 23 ]. To explore whether NOB can improve the mitochondrial function in activated astrocytes induced by hypoxia, we detected the mitochondrial membrane potential using a JC-1 Assay Kit.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that NOB plays an important role in modulating mitochondrial function, including influencing the mitochondrial membrane potential [ 20 , 21 , 22 , 23 ]. To explore whether NOB can improve the mitochondrial function in activated astrocytes induced by hypoxia, we detected the mitochondrial membrane potential using a JC-1 Assay Kit.…”
Section: Resultsmentioning
confidence: 99%
“…Nobiletin (NOB) is the active monomer isolated from CRP, with the molecular formula C 21 H 22 O 8 (the chemical structure is shown in Figure 1(a) ). NOB has been reported to possess anti-inflammatory [ 11 ], antiapoptotic [ 12 ], and antineurotoxic [ 13 ] functions. In the cardiovascular system, NOB has been reported to attenuate adverse cardiac remodeling in rats following MI by restoring autophagy flux [ 14 ] and regulating c-Jun N-terminal kinase (JNK) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The induced effect was related to the downregulation of translocation of AIF, and the upregulation of complex I activity, and the expression of antioxidant factors such as Nrf2 and heme oxygenase 1 (HO-1). Based on the acquired data, this study suggested that nobiletin might have promising neuroprotective action against neurodegenerative diseases such as AD and PD [155].…”
Section: Neurodegenerative Disordersmentioning
confidence: 87%